2007
DOI: 10.1029/2007gl029475
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial Maximum ocean thermohaline circulation: PMIP2 model intercomparisons and data constraints

Abstract: [1] The ocean thermohaline circulation is important for transports of heat and the carbon cycle. We present results from PMIP2 coupled atmosphere-ocean simulations with four climate models that are also being used for future assessments. These models give very different glacial thermohaline circulations even with comparable circulations for present. An integrated approach using results from these simulations for Last Glacial Maximum (LGM) with proxies of the state of the glacial surface and deep Atlantic suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
4
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 34 publications
11
153
4
1
Order By: Relevance
“…In Fig. 5 we show output from two National Center for Atmospheric Research Community Climate System Model version 3 (CCSM3) model simulations run for modern and LGM climates (33). The solid black lines, which mark the quasi-permanent sea ice line, shifted in excess of 5°latitude at the LGM, together with the area where the air-sea buoyancy flux is negative.…”
Section: Glacial Deep Ocean Stratification and Circulationmentioning
confidence: 99%
“…In Fig. 5 we show output from two National Center for Atmospheric Research Community Climate System Model version 3 (CCSM3) model simulations run for modern and LGM climates (33). The solid black lines, which mark the quasi-permanent sea ice line, shifted in excess of 5°latitude at the LGM, together with the area where the air-sea buoyancy flux is negative.…”
Section: Glacial Deep Ocean Stratification and Circulationmentioning
confidence: 99%
“…Since these were idealized experiments, no comparison to observations was possible. Otto-Bliesner et al (2007) compared AMOC in four Last Glacial Maximum simulations from the second phase of the Paleoclimate Modelling Intercomparison Project (PMIP2). These models gave very different glacial circulations and a comparison to Goosse et al (2010) paleoclimate proxy evidence indicated serious mismatches for several of the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, efforts, such as CLIMAP and more recently the Multiproxy Approach for the Reconstruction of the Glacial Ocean surface (MARGO), have attempted global syntheses of sea-surface temperatures [128,129]. Both of these types of compilations have been widely used by the data and modelling communities [130], highlighting the benefit of this sort of approach. But even in these few cases where reasonable amounts of data exist, there are still key gaps, such as at intermediate depth or in the Southern Ocean.…”
Section: (C) Focused Effort or Global Coverage?mentioning
confidence: 99%